Dynamic interactions between entrepreneurial domains and outcomes: The evolution of innovation ecosystems - Caterina Lucarelli; Nicoletta Marinelli; Alessandra Micozzi; Maria Zifaro; Maria Palazzo; Antonella Ferri (Journal of Innovation & Knowledge)
The actors and components of an entrepreneurial ecosystem coexist and interact continuously, leading to many mutual relationships. Existing studies favour a static approach to the investigation of innovation ecosystems, frequently neglecting the chains of connections between ecosystem domains and business results. This study attempts to fill this gap by studying the causality connections within innovation ecosystems, with a specific focus on the mutual causal links between ecosystem domains and entrepreneurial outcomes. Our empirical analysis is grounded in ecosystem archetypes centred on the entrepreneur, thus emphasising the centrality of the entrepreneur and their capability to absorb, capture, and exploit the surrounding ecosystem. Econometric models attempt to cope with the endogeneity issue and are estimated using the PSED II dataset. We find that ecosystem domains can be placed on a spectrum. This ranges from those with a direct influence on the desirable target of transforming a nascent entrepreneur into a new firm or on the decision to quit business projects to those exerting an indirect influence on the transition to a new firm in the form of higher-order connections among domains.